2020
DOI: 10.3389/fpsyg.2020.00247
|View full text |Cite|
|
Sign up to set email alerts
|

The Depression Anxiety Stress Scale-21 in Chinese Hospital Workers: Reliability, Latent Structure, and Measurement Invariance Across Genders

Abstract: The Depression Anxiety Stress Scale-21 (DASS-21) is an instrument in the assessment of mental health status. The current study recruited 1,532 Chinese hospital workers [74.4% female; mean age = 31.97 (SD = 9.70) years] to examine the reliability, latent structure, and measurement invariance of the DASS-21 between genders. The Cronbach's α values were greater than 0.90 for total score. This study examined four possible models of the DASS-21 using the confirmatory factor analysis (CFA) in Chinese hospital worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 54 publications
6
60
0
1
Order By: Relevance
“…Furthermore, we found no significant gender differences between our interest variables, except for men who reported higher levels of depression than women. This result is consistent with previous findings by Gong, Xie, Xu, & Yuejia (2010) and Jiang et al (2020), where men experienced higher depression levels than women. Nevertheless, our result could be affected by the low number of male subjects who took part in our study (N=19).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, we found no significant gender differences between our interest variables, except for men who reported higher levels of depression than women. This result is consistent with previous findings by Gong, Xie, Xu, & Yuejia (2010) and Jiang et al (2020), where men experienced higher depression levels than women. Nevertheless, our result could be affected by the low number of male subjects who took part in our study (N=19).…”
Section: Discussionsupporting
confidence: 94%
“…Mental health status was measured utilizing the Chinese version of DASS-21, which was retrieved from the DASS website [ 26 ]. DASS-21 was proven to be a valid screening instrument for assessing depression, anxiety, and stress among patients and general populations [ 11 , [27] , [28] , [29] , [30] ]. To date, the DSAA has been translated into 53 languages [ 26 ], which makes it widely accessible for practitioners and researchers across the globe.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the DSAA has been translated into 53 languages [ 26 ], which makes it widely accessible for practitioners and researchers across the globe. The Chinese version of DASS-21 has been shown to have good reliability in the Chinese population, including hospital workers, healthcare workers, university students, and adult residents in China [ [29] , [30] , [31] , [32] , [33] ]. The Chinese version of DASS-21 includes depression, anxiety, and stress subscales, each one containing 7 items for a total of 21 items.…”
Section: Methodsmentioning
confidence: 99%
“…The following guidelines are recommended for the interpretation of scores: In the depression section, score 0-9 shows normal or no depression, 10-13 shows mild depression, 14-20 shows moderate depression, 21-27 shows severe depression, and>27 indicates very severe depression. In the anxiety section, score 0-7 shows normal or no anxiety, 8-9 shows mild anxiety, 10-14 shows moderate anxiety, [15][16][17][18][19] shows severe anxiety, and>19 shows very severe anxiety. In the stress section, score 0-14 indicates normal or no anxiety, 15-18 indicates mild stress, 19-25 indicates moderate stress, 26-33 indicates severe stress, and>33 indicates very severe stress.…”
Section: Methodsmentioning
confidence: 99%
“…15 The DASS-21 is widely used to assess the core symptoms of anxiety and depression. 16 The DASS-21 has a strong interior reliability, convergent sustainability particularly for the depression scale. 17 Literatures showed that the prevalence of kidney disease may also indicate high prevalence of depression associated with renal disease; however, a large number of the studies are mostly focused on prevalence of kidney disease and their management rather than inspecting other associated risk factors.…”
Section: Introductionmentioning
confidence: 99%